Hydrogel formulations for biologicals: current spotlight from a commercial perspective. (9th February 2018) - Ickenstein, Ludger M; Garidel, Patrick
Hydrogels are, from a commercial perspective especially because of their ease of production, attractive sustained-release systems for high potent immunoglobulins with short circulation half-lives. Hydrogel formulations can reduce the dosing frequency while maintaining therapeutically relevant drug concentrations locally as well as systemically. However, hydrogels have only limited loading capacities and release hydrophilic immunoglobulins typically within hours or days, whereas weeks or months would be more preferable. Despite an evident medical need, the call for novel depot formulations seems to go unheard. This special report explores sought-after hydrogel properties, discusses arguments for using established versus novel excipients and provides selected examples for hydrogel formulations of biologicals that have proceeded into clinical development.